FACTORS AFFECTING THE HYDRODYNAMIC STATE OF THE SOKH GROUNDWATER DEPOSIT - B.D. Abdullaev; Q.R. Mingboyev; Z.M. Umarova; Z.B. Dadajonova; B.B. Dadajonov (Scholar Express Journal, 2023)
This study delves into the intensively developed Burganda massif in the southeastern Ferghana Valley, focusing on the technogenic impacts on groundwater deposits. The research examines the hydrogeological shifts triggered by irrigation, reclamation efforts, and industrial activities in neighboring Kyrgyzstan, notably affecting the Sokh River's flow distribution. It investigates the altered hydrogeological conditions, revealing rising groundwater levels, changes in hydrochemical composition, and challenges faced by regions like Rishtan. Employing hydrogeodynamic models and modern methodologies, the study outlines the hydrogeological characteristics of various aquifers, emphasizing their usage and susceptibility to contamination. It identifies factors contributing to groundwater changes, highlighting the dual influence of natural hydrometeorological and structurallithological factors alongside anthropogenic reclamation. Overall, this research sheds light on the intricate interplay between human interventions and natural processes, crucial for managing transboundary impacts on the geological environment
Keywords: Ground water level; hydrodynamics; flooding